Global burden of acute lower respiratory infection associated with human metapneumovirus in children under 5 years in 2018: a systematic review and modelling study. Issue 1 (January 2021) - Wang, Xin; Li, You; Deloria-Knoll, Maria; Madhi, Shabir A; Cohen, Cheryl; Ali, Asad; Basnet, Sudha; Bassat, Quique; Brooks, W Abdullah; Chittaganpitch, Malinee; Echavarria, Marcela; Fasce, Rodrigo A; et al.
Summary: Background: Human metapneumovirus is a common virus associated with acute lower respiratory infections (ALRIs) in children. No global burden estimates are available for ALRIs associated with human metapneumovirus in children, and no licensed vaccines or drugs exist for human metapneumovirus infections. We aimed to estimate the age-stratified human metapneumovirus-associated ALRI global incidence, hospital admissions, and mortality burden in children younger than 5 years. Methods: We estimated the global burden of human metapneumovirus-associated ALRIs in children younger than 5 years from a systematic review of 119 studies published between Jan 1, 2001, and Dec 31, 2019, and a further 40 high quality unpublished studies. We assessed risk of bias using a modified Newcastle-Ottawa Scale. We estimated incidence, hospital admission rates, and in-hospital case-fatality ratios (hCFRs) of human metapneumovirus-associated ALRI using a generalised linear mixed model. We applied incidence and hospital admission rates of human metapneumovirus–associated ALRI to population estimates to yield the morbidity burden estimates by age bands and World Bank income levels. We also estimated human metapneumovirus-associated ALRI in-hospital deaths and overall human metapneumovirus-associated ALRI deaths (both in-hospital and non-hospital deaths). Additionally, we estimated human metapneumovirus-attributable ALRI cases, hospital admissions, and deaths by combining human metapneumovirus-associated burden estimates and attributable fractions of human metapneumovirus in laboratory-confirmed human metapneumovirus cases and deaths. Findings: In 2018, among children younger than 5 years globally, there were an estimated 14·2 million human metapneumovirus-associated ALRI cases (uncertainty range [UR] 10·2 million to 20·1 million), 643 000 human metapneumovirus-associated hospital admissions (UR 425 000 to 977 000), 7700 human metapneumovirus-associated in-hospital deaths (2600 to 48 800), and 16 100 overall (hospital and community) human metapneumovirus-associated ALRI deaths (5700 to 88 000). An estimated 11·1 million ALRI cases (UR 8·0 million to 15·7 million), 502 000 ALRI hospital admissions (UR 332 000 to 762 000), and 11 300 ALRI deaths (4000 to 61 600) could be causally attributed to human metapneumovirus in 2018. Around 58% of the hospital admissions were in infants under 12 months, and 64% of in-hospital deaths occurred in infants younger than 6 months, of which 79% occurred in low-income and lower-middle-income countries. Interpretation: Infants younger than 1 year have disproportionately high risks of severe human metapneumovirus infections across all World Bank income regions and all child mortality settings, similar to respiratory syncytial virus and influenza virus. Infants younger than 6 months in low-income and lower-middle-income countries are at greater risk of death from human metapneumovirus-associated ALRI than older children and those in upper-middle-income and high-income countries. Our mortality estimates demonstrate the importance of intervention strategies for infants across all settings, and warrant continued efforts to improve the outcome of human metapneumovirus-associated ALRI among young infants in low-income and lower-middle-income countries. Funding: Bill & Melinda Gates Foundation.